Relationship Between Eco-Efficiency on Firm Value Moderated with Profitability and Leverage - Danang Satrio; Setiawan Kunto (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2019)
A large number of potential investors begin to consider the idea of responsible investment social responsibility. However, the debate over whether the value should be added as an environmental consideration for the stock selection process is still being debated. This study tries to improve the efficiency, profitability and leverage hypothesis of firm value. The sample used was 81 manufacturing companies listed on the Indonesia Stock Exchange and sent in 2014-2018 and using the rupiah. The data analysis tool used in this study is multiple linear regression estimated with OLS (Ordinary Least Square). The collected data is then processed and tested using SPSS 22 software. Based on the results of research analyzing the effect of eco-efficiency on firm value with profitability and leverage on the manufacturing industry listed on the Indonesia Stock Exchange during the period 2012 to 2016, it can be concluded that there is a significant positive effect between eco-efficiency on firm value.